PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA STAF PENGAJAR SDITA EL MA’MUR BOGOR (Lembaga Pengembangan Kinerja Dosen, 2023)
A conducive work environment is able to create a spirit of performance and encourage discipline in work. Every person in an organization always wants a conducive, safe and comfortable work environment. Work discipline can run well if it is supported by good environmental conditions. With the creation of discipline at work, it will certainly encourage productivity and enthusiasm at work. This study focuses on the effect of the work environment and work discipline on the performance of the teaching staf of SDITA eL Ma'mur Bogor. This type of research is quantitative. The population in this study was the teaching staff of SDITA eL Ma'Mur Bogor, amounting to 64 people. The data collection technique used a questionnaire which was distributed to 64 people using a saturated sample. The research method uses path analysis by examining the direct and indirect effects of the independent variable (exogenous variable) on the dependent variable (endogenous variable). The results showed that the work environment and work discipline together had an effect of 66.8% on performance with a significance probability of 0.000. The work environment has an influence on work discipline by 41% with a significance probability of 0.000. The work discipline variable is capable of being a mediating variable or an intermediate variable that links the indirect effect of the work environment on performance with a t-value of 2.289, which is greater than the t-table value